Current management and recent progress in desmoid tumors. (2022) - Zhou, Maggie Y.; Bui, Nam Q.; Charville, Gregory W.; Ghanouni, Pejman; Ganjoo, Kristen N.
Highlights: Desmoid tumors are rare soft tissue tumors that can have aggressive infiltrative growth and relapse locally. Desmoid tumors can impact functionality and cause treatment-related morbidity and mortality. Cryoablation and high-intensity focused ultrasound offer a less invasive approach than traditional surgical resection. Systemic therapy options include hormonal agents, nonsteroidal anti-inflammatory drugs, tyrosine kinase inhibitors, and anthracycline-based regimens. Emerging therapies include gamma-secretase inhibitors and beta-catenin inhibitors. Current management and recent progress in desmoid tumors Abstract: Desmoid tumors are rare soft tissue tumors that can have aggressive infiltrative growth and relapse locally. Desmoid tumors can impact functionality and cause treatment-related morbidity and mortality. Here, the authors review current management strategies and avenues for further investigation. As part of the evolution of therapy away from primary surgical approaches to less invasive options, image-guided ablation has been accepted as less morbid and include cryoablation and high-intensity focused ultrasound. Systemic therapy options currently include hormonal agents, nonsteroidal anti-inflammatory drugs, tyrosine kinase inhibitors, and anthracycline-based regimens. Hormonal agents and nonsteroidal anti-inflammatory drugs have benign side effect profiles but generally limited efficacy. Anthracycline-based therapies are limited by the risk of secondary malignancies and cardiomyopathy. Tyrosine kinase inhibitors are well studied, and sorafenib is now one of the most utilized therapies, though limited by its side effect profile. Nirogacestat (PF-0308401) is an investigational small molecule gamma-secretase (GS) inhibitor that has demonstrated efficacy in phase 1 and II trials. A phase III trial investigating patients with desmoid tumors or aggressive fibromatosis is estimated to be completed December 2021 (NCT03785964). In addition to nirogacestat, the gamma-secretase inhibitor AL102 is being investigated for the treatment of patients with progressing desmoid tumors in the phase II/III RINGSIDE trial. Finally, the beta-catenin inhibitor Tegavivint (BC2059) is being investigated in a phase 1 open-label trial in patients with a proven primary or recurrent desmoid tumor that is unresectable and symptomatic or progressive.